A Literature Review on the Separation of Chemical Compounds - Husien, Nemah Sahib Mohammed; Gafel, Rajaa Abd Alameer; Jaffer, Noor Dia (American International Journal of Multidisciplinary Scientific Research, 2018)
This  literature  involved  explanation  about  separation organic  components  in  mixture such  as(chromatography ,extraction ,filtration, centrifuge…) , principles of separation  , methods of separation ,types of separation , purification  of separated  compounds , conditions of separation , physical and chemical properties of  mixture.